GVC exporter performance during the COVID-19 pandemic: The role of supply bottlenecks - Laura Lebastard; Marco Matani; Roberta Serafini (European Central Bank (ECB), 2023)
This paper provides an analysis of the impact of the COVID-19 pandemic on exporting firms, focusing on the role of supply bottlenecks. Based on monthly transaction-level data for the universe of French exporters over the period January 2020-December 2021, we find that participation in global value chains increased firms' vulnerability to the COVID-19 shock, in terms of both export performance and probability of survival in the export market, the negative impact of supply disruptions being higher for relatively more downstream firms. At the same time, the results suggest that exporting firms benefited from sourcing of core inputs from different countries, supporting the hypothesis that diversification in global value chains fosters supply-chain resilience.
Keywords: D22; F14; F61; 330; Pandemic; Shock Transmission; Global Value Chains; Diversification; Upstreamness